The prevalence of coronary artery anomalies in adults: Studied with computed tomography coronary angiography - Ilić Dragana; Stojanov Dragan; Koraćević Goran; Petrović Slađana; Radovanović Zoran; Arsić Stojanka (Vojnosanitetski Pregled)
Background/Aim. Coronary artery anomalies are an uncommon but important cause of chest pain, and in some cases of hemodynamically significant abnormalities, sudden cardiac death. The aim of the research was to establish the prevalence of the coronary arteries anomalies in our population. Methods. The study group included 1,562 patients (810 men, 752 women, average age 64.3 ± 12.0 years; range 32–80 years) who were scheduled for 64-slice computed tomography (MSCT), which enables detailed visualization of coronary arteries and heart anatomy. All examinations were made due to suspicion (atypical chest pain, angina equivalent symptoms or multiple risk factors for cardiovascular disease) or assumption of progression of coronary artery disease. Results. From January 2010 till December 2014 a total number of 1,562 patients were sent for evaluation of coronary arteries. The coronary anomalies were found in 45 (2.88%) patients. The most frequent coronary anomaly seen in our population group was absence of left main trunk with the separate origin of the left anterior descending artery (LAD) and left circumflex artery (LCx) originating from a left coronary sinus (LCS). This was found in 12 patients (an incidence of 0.77% or 26.7% of all coronary anomalies). Anomalous location of coronary ostium outside normal aortic sinuses in our study was present as right coronary artery (RCA) that arises from left anterior sinus in 5 (0.32%) patients and left coronary artery from non-coronary sinus in two (0.13%) patients. Conclusion. Knowledge of anomalies of the coronary arteries and their recognition on the multislice computed tomography is of great importance for the further planning of a possible therapeutic treatment. Coronary anomalies that are considered insignificant will require no further therapeutic treatment. But the detection of malignant coronary anomalies will certainly save many lives.